Assessing The Key Photophysical Properties of Triangulenium Dyes for DNA Binding by Alteration of the Fluorescent Core. Issue 7 (23rd December 2020) - Lewis, Benjamin W.; Bisballe, Niels; Santella, Marco; Summers, Peter A.; Vannier, Jean‐Baptiste; Kuimova, Marina K.; Laursen, Bo W.; Vilar, Ramon
Abstract: Four‐stranded G‐quadruplex (G4) DNA is a non‐canonical DNA topology that has been proposed to form in cells and play key roles in how the genome is read and used by the cellular machinery. Previously, a fluorescent triangulenium probe (DAOTA‐M2 ) was used to visualise G4s in cellulo, thanks to its distinct fluorescence lifetimes when bound to different DNA topologies. Herein, the library of available triangulenium probes is expanded to explore how modifications to the fluorescent core of the molecule affect its photophysical characteristics, interaction with DNA and cellular localisation. The benzo‐bridged and isopropyl‐bridged diazatriangulenium dyes, BDATA‐M2 and CDATA‐M2 respectively, featuring ethyl‐morpholino substituents, were synthesised and characterised. The interactions of these molecules with different DNA topologies were studied to determine their binding affinity, fluorescence enhancement and fluorescence lifetime response. Finally, the cellular uptake and localisation of these optical probes were investigated. Whilst structural modifications to the triangulenium core only slightly alter the binding affinity to DNA, BDATA‐M2 and CDATA‐M2 cannot distinguish between DNA topologies through their fluorescence lifetime. It is argued theoretically and experimentally that this is due to reduced effectiveness of photoinduced electron transfer (PET) quenching. This work presents valuable new evidence into the critical role of PET quenching when using the fluorescence lifetime of triangulenium dyes to discriminate G4 DNA from duplex DNA, highlighting the importance of fine tuning redox and spectral properties when developing new triangulenium‐based G4 probes. Abstract : Two new optical probes for DNA based on diazatriangulenium dyes featuring ethyl‐morpholino substituents are reported. Upon interaction with duplex and quadruplex DNA, these two probes switch on their fluorescence intensity and change their emission lifetime (although the latter is not dependent on the DNA topology). This has allowed study of the cellular uptake and localisation of the two new probes in cancer cells. Whilst structural modifications to the diazatriangulenium core only slightly alter the binding affinity to DNA, their cellular localisation is significantly altered.